Examining the Reading Aloud Speeds of the Secondary School Students - Mete, Gulsah (Asian Journal of Education and Training, 2020)
Having a critical role in both academic and social lives, reading fast and comprehension are necessary skills for today’s individuals. The factors affecting these skills of adolescent learners are needed to examine. With an intention to provide significant results to the literature, this study aimed to examine if there is a difference between the secondary school students’ reading aloud speeds and the variations as the type of the text, their gender, and their classroom levels. 40 students, of whom were 20 girls and 20 boys, from a secondary school attended to the study. They varied across the classroom levels as well. Accordingly, 10 of those students were 5th, 10 of them were 6th, 10 of them were 7th, and 10 of them were 8th graders. In order to collect data, a narrative text (a story) and an informative text (an essay) were utilized to test the students’ reading aloud speeds. The findings were obtained through the standard deviation calculations. Accordingly, the study revealed that the reading speeds of the secondary school students change according to the text type, their gender and classroom levels.